2020
DOI: 10.32677/ijch.2020.v07.i01.008
|View full text |Cite
|
Sign up to set email alerts
|

Short-term safety and beneficial effects of hydroxyurea therapy in children with sickle cell disease

Abstract: Introduction: Worldwide, sickle cell disease (SCD) is the most common hemoglobinopathy among which SS pattern is more common. Although hydroxyurea (HU) is approved by the Food and Drug Administration for the treatment of recurrent moderate-to-severe painful crises in pediatric sickle cell anemia, there is a fear of toxicities. Objectives: The objectives of the study were to evaluate the short-term safety and beneficial effects of low-dose HU therapy in SCD (SS pattern) children. Materials and Methods: This pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…While selected 10 studies 20 , 22 - 24 , 26 , 27 , 29 , 30 , 32 , 33 assessed the efficacy/toxicity of HU therapy in SCD, two articles each were on beta-thalassaemia 21 , 28 and HbSD-Punjab 25 , 31 . Of the total 14 studies reviewed, five (35.7%) studies 20 , 22 , 27 , 29 , 31 were conducted in paediatric patients, six (42.8%) 21 , 24 , 25 , 30 , 32 , 33 in adults patients and three (21.4%) in others 26 - 28 in paediatric as well as adult patients with SCD. The duration of both observation and the follow up of patients, however, varied in the studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While selected 10 studies 20 , 22 - 24 , 26 , 27 , 29 , 30 , 32 , 33 assessed the efficacy/toxicity of HU therapy in SCD, two articles each were on beta-thalassaemia 21 , 28 and HbSD-Punjab 25 , 31 . Of the total 14 studies reviewed, five (35.7%) studies 20 , 22 , 27 , 29 , 31 were conducted in paediatric patients, six (42.8%) 21 , 24 , 25 , 30 , 32 , 33 in adults patients and three (21.4%) in others 26 - 28 in paediatric as well as adult patients with SCD. The duration of both observation and the follow up of patients, however, varied in the studies.…”
Section: Resultsmentioning
confidence: 99%
“…Efficacy & effectiveness of hydroxyurea (HU) : It was noted that the majority of the studies indicated the efficacy of low-dose HU therapy in reducing the frequency of pain crises, blood transfusions and hospitalization. Of the 14 studies, 12 used the fixed-dose method 20 , 22 - 26 , 28 - 33 , and two used the standard dose escalation method 21 , 27 . In the two studies that used the dose escalation method, while one study started with a low dose of 10 mg/kg/day and escalated to 15 mg/kg/day, the other one started from 15 mg/kg/day and escalated to 30 mg/kg/day 21 , 27 .…”
Section: Resultsmentioning
confidence: 99%
“…Prevalence of allo-immunization was higher in SCD than in β-thalassaemia major Dave et al [ 56 ] A longitudinal descriptive study of patients with SCD from tribal area of Gujarat, India SCD comprehensive care programme increased the coverage of HU from 3.5 to 88%. Rate of transfusion reduced significantly after the enrolment with the programme (27.4 vs 17.8 per 100 patient years) Good quality care can be provided even for the economically deprived remote communities with SCD Somkuwar et al [ 57 ] A prospective cohort study involving Hb SS children from Maharashtra, India After the HU therapy, rate of acute pain crisis and blood transfusion reduced significantly ( p = 0.001) Low-fixed dose HU therapy is safe and effective for Indian Hb SS children Sinha et al [ 58 ] A descriptive survey which projected the blood and budgetary requirement for haemoglobinopathies in India (2017–2026) Annual requirement of blood for SCD would increase by 0.99 million units/year. Projected requirement of blood in 2026 was 9.24 million units Widespread efficient and effective preventive strategies are urgently required to cope with the sharply increasing demand of blood Jain et al [ 59 ] A prospective cohort comparison study involving Hb SS patients from Nagpur, India 26 (33%) Hb SS patients received 74 transfusions (mean 2.8 episodes/patient) Pre-transfusion Hb was below 6 g/dl in 67% of patients.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies practiced HU therapy in accordance with first recommendation (Grade 1A) which is the usage of HU when adult Sickle cell anaemia (SCA) patients’ experience ≥ 3 moderate to severe pain crises in a 12-month period [ 29 31 , 52 , 53 ]. Seven studies practiced HU therapy in accordance with 2 nd , 3 rd and 4 th recommendations (Grade 1 B) suggesting the usage of HU when adult SCA patient has a history of ACS or symptomatic anaemia; children with SCA experience ≥ 3 moderate to severe pain crises in 12-month time period or having a history of ACS or symptomatic anaemia [ 29 32 , 34 , 35 , 57 ]. In addition, five studies practiced HU therapy in accordance with recommendation 6 (usage of HU in SCA patients who have a history of stroke) [ 29 , 30 , 34 , 35 , 57 ], and two studies [ 29 , 42 ] in accordance with recommendation 7 (usage of HU in adult Hb S-β+ thalassaemia patients who experience ≥ 3 pain crises in 12-month period or having a history of ACS).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation